Demystifying the empirical link between safety climate, safety communication, work environment, and unsafe behaviour at work - Johanim Johari; Tan, Fee Yean; Zurina Adnan (Penerbit Universiti Kebangsaan Malaysia, 2017)
The primary objective of this study is to examine the predicting roles of safety climate, safety communication, and work environment on unsafe behaviour. A survey was carried out among employees in manufacturing companies in Klang Valley. A total of 108 employees reported on safety climate, safety communication, work environment as well as their engagement in unsafe behaviour at work. Data was analyzed using Statistical Package for Social Sciences (SPSS) version 17.0. The findings reported that safety climate and work environment had a significant impact on respondents’ unsafe behaviour. Safety communication, on the other hand, had no bearing on unsafe behaviour among respondents in this study. Drawing on the findings, discussions elaborated on the importance of safety climate and work environment in curbing unsafe behaviour among employees. Theoretical and practical ramifications as well as directions for future research and conclusion of the study are put forward.